Peran Guru Bimbingan Dan Konseling (BK) Dalam Membentuk Pemahaman Dan Kepatuhan Siswa Terhadap Peraturan Sekolah Di MTSN 2 Medan - Miswati, Miswati; Tambusai, Khairuddin (Universitas Mathla'ul Anwar Banten, 2025)
This study aims to describe the role of Guidance and Counseling (BK) teachers in shaping students' understanding and compliance with school regulations at MTSN 2 Medan. This study uses a qualitative approach with data collection techniques in the form of interviews, observation, and documentation. Through an educational and humanistic approach, BK teachers provide guidance services in the form of orientation, classical guidance, individual counseling, and case conferences to address violations that occur. School regulations are conveyed in a communicative manner so that students not only understand the contents of the regulations, but also understand the reasons and values behind them. BK teachers also implement a violation point system and SPO (Parental Statement Letter) as collaborative development instruments. After conducting various analyses, the results of this study can be concluded that Guidance and Counseling (BK) teachers have a strategic role in shaping students' understanding and compliance with school regulations at MTSN 2 Medan. This role is realized through guidance services that are educational, collaborative, and humanistic, including orientation, classical guidance, individual counseling, and involvement in case conferences. Guidance and counseling teachers not only perform supervisory functions but also play an active role in developing students' character through persuasive communication and the implementation of structured guidance systems, such as violation points and Parental Statement Letters (SPO). Overall, the approach implemented by guidance and counseling teachers has proven effective in reducing violation rates and encouraging the internalization of disciplinary values.